2022
DOI: 10.1101/2022.12.27.522030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of emergent toxigenic M1UKStreptococcus pyogenesand associated sublineages

Abstract: Emm1 Streptococcus pyogenes is a successful, globally-distributed epidemic clone that is regarded as inherently invasive. An emm1 sublineage, M1UK, that expresses increased SpeA toxin, was associated with increased scarlet fever and invasive infections in England in 2015/2016. Defined by 27 SNPs in the core genome, M1UK is now dominant in England. To more fully characterise M1UK, we undertook comparative transcriptomic and proteomic analyses of M1UK and contemporary non-M1UK emm1 strains (M1global). Just seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Typing results have been reported for 13 child deaths, of which nine were emm 1, three were emm 12 and one was emm 77. Whole genome sequencing of all typed invasive and non-invasive isolates indicates that there has been no obvious expansion of a single clone for those emm types, however, the majority of the emm 1 isolates were part of the emm 1 M1UK clone, first detected in 2010, for which upregulation of SpeA expression, a virulence factor of Streptococcus pyogenes, has been demonstrated [7,8].…”
Section: Emm Typesmentioning
confidence: 99%
“…Typing results have been reported for 13 child deaths, of which nine were emm 1, three were emm 12 and one was emm 77. Whole genome sequencing of all typed invasive and non-invasive isolates indicates that there has been no obvious expansion of a single clone for those emm types, however, the majority of the emm 1 isolates were part of the emm 1 M1UK clone, first detected in 2010, for which upregulation of SpeA expression, a virulence factor of Streptococcus pyogenes, has been demonstrated [7,8].…”
Section: Emm Typesmentioning
confidence: 99%
“…We recently reported that strains from the M113SNP intermediate sublineage produce negligible amounts of SpeA, similar to M1global (9). Phylogenetic analysis of Australian sequences (9) shows the M113SNP sublineage to be present in Australia too (Figure 1A).…”
Section: Introductionmentioning
confidence: 76%
“…We recently reported that strains from the M113SNP intermediate sublineage produce negligible amounts of SpeA, similar to M1global (9). Phylogenetic analysis of Australian sequences (9) shows the M113SNP sublineage to be present in Australia too (Figure 1A). Strains from the M123SNP sublineage, in contrast, produce SpeA at an increased level that is indistinguishable from M1UK isolates (9).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations